Dinamika Komunikasi Interpersonal Pasangan Militer Dalam Pernikahan Hasil Perjodohan - Aurellia Calista Gunawan; Ratu Laura Mulia Baskara Putri (Jayapangus Press, 2026)
Arranged marriages among military couples involve distinctive interpersonal communication dynamics because partners must develop intimacy after marriage while facing military demands, including mobility, assignments, limited time together, and long-distance relationships. This study aims to analyze interpersonal communication dynamics among military couples in arranged marriages and identify the interpersonal relationship patterns formed through communication. This research employed a qualitative method with a phenomenological approach. Data were collected through in-depth interviews and documentation and analyzed using the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing/verification. The findings show that emotional closeness between partners does not emerge instantly but develops gradually through adaptation, openness, discussion, compromise, and continuous communication. Couples manage differences in culture, character, habits, and perspectives through direct interaction and communication media when separated by military duties. The study reveals relational dialectical tensions, including openness and protection, autonomy and connection, as well as predictability and novelty. Family support and respect for parents strengthen the couples’ commitment to maintaining their marriages. Therefore, interpersonal relationships are constructed through understanding and adjustment. In conclusion, interpersonal communication serves as the foundation for building trust, managing conflict, strengthening emotional intimacy, and sustaining marital harmony among military couples in arranged marriages.